EuReCa Serbia 2014-2021 - Analysis of data on non-initiation of CPR in relation to gender of patients with OHCA - Medic, Sara; Ristic, Jovana; Vasilic, Milica; Suskovic, Rajka; Bandulaja , Marina; Lazic, Aleksandra; Ranđelovic , Suzana (Journal Resuscitatio Balcanica, 2024)
Aims: . The analysis aimed to investigate differences in the initiation of cardiopulmonary resuscitation based on gender, as well as differences between geneders considering location of the cardiac arrest, etiology, and age.  Material and methods: This study analyzed epidemiological data on out-of-hospital cardiac arrest from the EuReCa study, collected via the European Resuscitation Council and EuReCa ONE protocol. The dataset, covering October 1, 2014, to December 31, 2021, was created using data from 16 municipalities in Serbia, representing 24.13% of the population.  Results: Data revealed a total of 8,349 OHCA cases, with CPR initiated in 2,758 cases (33.1%). Statistically significant differences in CPR initiation were observed between genders, with a higher initiation rate for males (41.7%) compared to females (23.5%) (χ2 (1) = 307.312; p
Keywords: cardiopulmonary resuscitation; out-of-hospital cardiac arres; epidemiology OHCA; EuReCa SWerbia